Peter & Ernesto : the lost sloths - Annable, Graham (First Second, 2019)
Peter and Ernesto loved their tree. Then a hurricane came and blew it away! Now, Peter, Ernesto, and the rest of their sloth friends must venture into the jungle to find a new-great-tree. But the jungle is full of dangers, including angry ants, slithering snakes, and a ravenous jaguar! Can cautious Peter and confident Ernesto work together to keep their tribe safe? They'll have to, if they want to find the perfect tree to call home!